The Opinion of General Practitioners, Medical Students, and Other Medical Specialists on Palliative Care in Bulgaria. (30th January 2014) - Foreva, G.; Asenova, R.; Semerdjieva, M.
Abstract : In Bulgaria, the patient is entitled to palliative care in case of incurable disease with an unfavourable prognosis. Palliative care is provided by the family doctor/GP and institutions. Literature on palliative care providing is scarce. The objective of the study was to investigate the opinion of general practitioners, medical students, and other medical specialists working in institutions on palliative care. Method. We have developed a structured questionnaire. Descriptive statistics have been calculated for all items. Differences between groups have been compared usingu -criterion. Level of significance wasP < 0.05 . Data has been analyzed using SPSS v. 16. Results. A total of 518 respondents completed the survey. Lack of appropriate organisation and financing has been pointed out by all participants. The GP's role in palliative care providing has been described as a contradictory one. The criteria on the basis of which the patients are eligible for palliative care have been arranged in the same way by all respondents, but GPs chose the longest temporal indicator. Quality assessment has not been applied. 2/3 of respondents demanded palliative care training. Conclusion. On the whole, the investigated groups differed to some extent in their opinion on palliative care both on conceptual and practical levels.